Albert de Pouvourville’s Occultisme Colonial - Marino, Davide (Numen, 2023)
Albert de Pouvourville (1862–1939), better known by his nom de plume Matgioi, was one of the most noticeable characters of the nineteenth-century French occult milieu. In addition to his prominence in fin-de-siècle occult Paris, de Pouvourville also served as a soldier in Indochina, and after the end of his military career he continued to play an important role in French colonialism. This article aims to describe both de Pouvourville’s occultist and colonialist production and argues that they should be understood as two parts of a coherent intellectual trajectory, characterized by two fundamental elements of de Pouvourville’s worldview: “elitism” and “colonial Darwinism.” From gender and race to initiation and opium consumption, de Pouvourville’s “discourse on the Far East” is a form of “colonial occultism”: a peculiar mix of imperialist hegemonic aspirations and spiritual thirst for “the wisdom of the East.”
Created from Fastlane, Scopus look-up
Keywords: Albert de Pouvourville; colonialism; Indochina; Matgioi; occultism; René Guénon

Mircea Eliade and René Guénon Patterns of Initiation and the “Myth of Affinity” - Marino, Davide (Aries - Journal for the Study of Western Esotericism, 2022)
This article analyses the intellectual relationship between the historian of religions Mircea Eliade and the French esotericist René Guénon. Many scholars have argued for the “the myth of affinity”, a theory according to which Eliade would have subscribed to Guénon’s worldview (Traditionalism). The proponents of this thesis believe that Eliade opportunistically masked his Traditionalism for fear of being considered not sufficiently “scientific” for the academic career he aspired to. This article argues against such a theory and intends to demonstrate how the “myth of affinity” arose from a series of misunderstandings that occurred in the circle of Guénon’s closest associates, probably fuelled by Eliade himself. A comparison of Guénon and Eliade’s works on the theme of initiation will be used to dismiss “the myth of affinity” by indicating the irreconcilable theoretical distance between Traditionalism and Eliadian hermeneutics.
Created from Fastlane, Scopus look-up
Keywords: esotericism; initiation; Mircea Eliade; myth; René Guénon; traditionalism

The Daoist who wasn’t - Marino, Davide (Appropriating the Dao: The Euro-American Esoteric Reception of China, 2024)
This chapter explores the intellectual and personal relationship between the French occultist Albert de Pouvourville (better known as “Matgioi”) and two of his Vietnamese informants: Nguyễn Văn Luật and his younger son Nguyễn Văn Cang. De Pouvourville had encountered the two between 1887 and 1892 while he was serving as a soldier in the context of the French colonial wars. The names Văn Luật and Văn Cang appeared as authors of a series of French publications in the first decade of the twentieth century. The two are commonly believed to be the only Vietnamese active in fin de siècle French occultism. Through a detailed analysis of all sources available, this chapter proves that Văn Luật and Văn Cang never wrote the texts that were published as authored by them. Instead, their status of “real Orientals” was exploited by de Pouvourville in his attempt to affirm the validity of his interpretation of Daoism. This process of borrowing the authority of (semi)invented “oriental masters” is one of the possible modes of interaction between “Eastern” and “Western” esotericis

The Path to Gnosis: a Microhistory - Marino, Davide (Vienna Journal of East Asian Studies, 2024)

The Tao of Julius Evola - Marino, Davide (Vienna Journal of East Asian Studies, 2024)